Comparing social costs of public transport networks structured around an Open and Closed BRT corridor in medium sized cities. (August 2020) - Proboste, Francisco; Muñoz, Juan Carlos; Gschwender, Antonio
Highlights: A continuum approx model for Open and Closed BRT operational schemes is formulated. The model is adapted and solved for Valdivia (Chile), yielding comparative indicators. The results of the model are applied to the topography and road network of Valdivia. An estimation of the impact of both schemes for a real case is provided. According to the model, an Open BRT should be preferable for the context of this city. Abstract: Bus Rapid Transit (BRT) has proven to be an effective and affordable transportation option for large-sized cities. In these cities, BRT is usually considered an effective complement or substitute for rail-based systems, playing a key role in complex multimodal networks with several massive transport corridors. More recently, medium-sized cities of less than 200, 000 inhabitants have also considering implementing BRT as a means of mass transit. These cities usually need only a few of these massive transport corridors (often just one), and they must decide how to structure their services. This report discusses which of the two types of BRT-based networks is best for the social interest in the case of medium-sized cities: (1) Closed BRT, in which buses operating inside and outside the corridor are separated and have different designs, or (2) Open BRT, in which the same buses operate inside and outside the corridor, entering and exiting at different points along a route. To answer this question two models with different levels of detail in terms of a city's characteristics were developed to represent both agency and user costs. In the first model a classic idealized city approach is addressed, while in the second model the problem is solved for the specific geographic characteristics and constraints of a real city. The results based on both models show that when it is optimally configured, Closed BRT networks offer mid-sized cities higher frequencies and lower waiting times. However, these benefits do not offset the cost associated with higher number of transfers that Closed BRT networks require, as compared to Open BRT networks. Transfers not only affect users due to the transferring experience, but also end up making the entire system slower. Overall, Open BRT shows significantly less Total Costs than Closed BRT in most of the scenarios that were analyzed.